Parental concerns regarding young children and digital technology. An exploratory qualitative investigation in three European countries - Brito, Rita (2021)
One of the effects of the development and widespread diffusion of digital technologies is that in contemporary homes children are being exposed to those technologies since birth. The present study aims to identify the general 'climate of concern' and to map specific worries that parents have with respect to their young children's digital lives. The study was theoretically framed by the intersection of parental mediation theory with media panics theory, and relied on data collected in three European countries (Portugal, Romania and Slovenia) as part of JRC project Young Children (0-8) and digital technologies. The data were collected in 2015, through family visits, this paper focusing on semi structured interviews that took place with parents. The results show that parents of children under 8 years old are concerned about health-related issues, screen addiction, exposure to age-inappropriate content, social exclusion by absence or under use of digital media, concerns of losing opportunities for essential (non-digital) childhood experiences, bad school performance and learning the "right" skills for the future. If some of these concerns echo public discourse on the risks of technology, parents in our study trimmed these fears and adjusted them to their current situation and their parental mediation practices.